Halal certification in food products : Science mapping of present and future trends - Muhammad Ashraf, Fauzi; Noor Saadiah, Mohd Ali; Nazirah, Mat Russ; Fazeeda, Mohamad; Battour, Mohamed Mohamed; Nor Nadiha, Mohd Zaki (Emerald Publishing, 2024)
This study aims to evaluate the knowledge structure of halal certification in food and beverages. The growth of the Muslim population and the expanding economic activities among the Muslim community have necessitated extensive and comprehensive halal certification, particularly in food and beverage products. Design/methodology/approach: Through a science mapping approach, this study explores the knowledge structure based on past publications in food and beverages and its association with halal certification, logos and brands. Applying bibliographic coupling and co-word analysis, the present and future trends of halal certification in food and beverages are explored by presenting a network visualization to present the underlying themes and research streams. Findings: The main finding from recent and emerging themes shows that the pivotal perspective is increasing consumers’ knowledge and awareness of halal-certified food products. Future trends stemming from the co-word analysis suggest the importance of exploring consumer halal food product determinants. Originality/value: This study is relevant to stakeholders, scholars and practitioners, particularly in disseminating information and voice on the importance of halal-certified food products that are recognized as having better quality and contributing to environmental sustainability.